Spatial targeting of ICT-based weather and agro-advisory services for climate risk management in agriculture - Gangopadhyay, Prasun K.; Khatri-Chhetri, Arun; Shirsath, Paresh Bhaskar; Aggarwal, Pramod K. (Springer, 2019)
The increasing frequency of climatic risks, such as flood, drought, heat and cold waves, is causing significant loss of farm productivity and income in agriculturally dependent communities. Timely availability of reliable information on weather conditions, agro-advisories, and market information can help to minimize losses in agriculture. This paper presents a scientific and integrated approach to identify areas of high agriculture vulnerability to climate change and availability of ICT services for dissemination of CSA information in the vulnerable areas. This study was illustrated for India where the majority of the population depends on agriculture for their livelihoods, and this sector is highly vulnerable to climate change. The study presents four regions: i) high agriculture vulnerability and low ICT services, ii) high agriculture vulnerability and high ICT services, iii) low agriculture vulnerability and low ICT services, and iv) low agriculture vulnerability and high ICTservices. Thismethodology, which is simple, uses available data, and is easy to apply, can be useful to prioritize locations for climate-smart interventions, mode of CSA information dissemination using ICT services, and increase coverage of agro-ICT services through development of ICT services in the locations where climate change impact is high and ICT services are very low. This study also showed that there is a need to improve the quality of existing climate information and agro-advisory services in the climate risk-prone areas.